Effect of water stress and varieties on the bioherbicidal effectivity of sorghum aqueous extracts - Susilo, E.; Setyowati, N.; Supriyanti, Y. I. (International Journal of Agricultural Technology, 2025)
The 5% water extract from Super 1 sorghum variety irrigated every 5 days, Suri 4 irrigated every 4 and 5 days, and Mandau irrigated every five days was more toxic compared to other treatments, as indicated by the lowest percentage of seed germination, seedlings fresh weight, fresh weight of plumule and radicle, and plumule and radicle length, as well as the higher percentage of dead seedlings and fresh weight of dead seedlings. These findings suggested that the Super 1, Suri 4, and Mandau sorghum varieties, with irrigation frequencies of 4 or 5 days, can produce allelopathic compounds that can be used as bioherbicides to control broadleaf weeds.